2015
DOI: 10.1007/s11164-015-2208-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, antioxidant and anticancer screenings of berberine–indole conjugates

Abstract: A variety of heterocyclic nitrogen cores in the form of indole moieties were linked to the natural isoquinoline alkaloid molecule berberine to achieve anticipated antioxidant and anticancer properties. An efficient synthetic pathway afforded final compounds 5a-j, which were tested in vitro for antioxidant potency using 1,1-diphenyl-2-picrylhydrazyl radical (DPPH) and 2,2 0 -azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt radical (ABTS) bioassays, and for anticancer activity using sulforhodami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The inclusion of antioxidants to the conducted radical cation decreases it to ABTS, identifying a decolourization. In this technique, an antioxidant is included in a pre-formed ABTS radical solution, and after a set period, the staying ABTS _ + is quantified spectrophotometrically at 734 nm [ 42 , 43 ]. In the current study, all extract/fractions except petroleum ether fraction and positive control (ascorbic acid) exhibited a significant, dose-dependent radical scavenging activity ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion of antioxidants to the conducted radical cation decreases it to ABTS, identifying a decolourization. In this technique, an antioxidant is included in a pre-formed ABTS radical solution, and after a set period, the staying ABTS _ + is quantified spectrophotometrically at 734 nm [ 42 , 43 ]. In the current study, all extract/fractions except petroleum ether fraction and positive control (ascorbic acid) exhibited a significant, dose-dependent radical scavenging activity ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Two controls were applied for this test: a negative control (blank) containing of methanol (20 μL) and the DPPH radical solution (180 μL) and a positive control including the referrals anti-oxidant (Ascorbic acid) in methanol and DPPH radical solution. The results of this bioassay, RSA% (the radical scavenging activity in percentage) was determined according to Mensor et al (Mensor et al, 2001, Mistry et al, 2015) as described in the below equation:%Scavenging=Absorbance of blank-Absorbance of testAbsorbance of blank×100…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion of anti-oxidants to the conducted radical cation decreases it to ABTS, identifying a decolourization. In this technique, an antioxidant is included in a pre-formed ABTS radical solution, and after a set period, the staying ABTS •+ is quantified spectrophotometrically at 734 nm (Molyneux, 2004, Mistry et al, 2015). The ABTS •+ was created by responding 7 mM ABTS in H 2 O with 2.45 mM potassium persulfate (K 2 S 2 O 8 ), saved in the dark at room temperature for 12–16 h before use (the radical was constant for more than two days under these conditions).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BBR derivates, containing phenolic hydroxy groups, have been reported with enhanced antioxidant activity. At the same time, 8-oxocoptisine, 16 indole, 17 piperazine 18 and benzothiazole 19 derivatives of berberine have also been developed in recent years, while the C-9 position modification of benzoic acid was seldom reported. In our previous work, we designed and synthesized a series of berberine derivatives, and demonstrated that the introduction of an aromatic nucleus on the C-9 position of berberine had important influences on hypoglycemic 20 and anti-inflammatory activities, 21 which were closely related with oxidative stress.…”
Section: Introductionmentioning
confidence: 99%